An efficient and forward-secure lattice-based searchable encryption scheme for the Big-data era. (December 2021) - Islam, SK Hafizul; Mishra, Nimish; Biswas, Souvik; Keswani, Bharat; Zeadally, Sherali
Abstract: As the amount of data generated by scaled systems in Electronic Medical Records (EMRs) and the Industrial Internet of Things (IIoT) keeps increasing, third-party servers are essential for data storage and manipulation, and with them come privacy concerns. Encrypting the uploaded data strips the server's ability to search over it for keywords: a highly desirable requirement in some use-cases as EMRs and IIoT. Subsequent efforts at constructing efficient and secure post-quantum searchable encryption schemes have failed to prevent a curious server from launching inside offline keyword guessing attack. For every intended receiver, the data owner performs computation separately, implying the requirement of prior knowledge about recipients (which is not practical in a use-case such as EMR) and a high overhead is incurred in the big data era. We provide a detailed cryptanalysis of existing theoretically secure schemes and leverage blockchain for load balancing. We then propose a scheme secure from an honest-but-curious server. We also present a detailed comparative analysis with existing schemes as well as efficient methods to mitigate blockchain overheads. Highlights: Proposed a post-quantum forward-secure lattice based searchable encryption scheme The scheme is secure in threat model: 'honest-but-curious server' The scheme offers effective load balancing with the use of blockchain The scheme delegates computational and storage load from server to users